1981
DOI: 10.1111/j.1651-2227.1981.tb05544.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Intermittent Positive Pressure Ventilation by Nasal Prongs in Intractable Apnea of Prematurity

Abstract: In order to avoid endotracheal intubation in very small newborn infants requiring prolonged intermittent positive pressure ventilation (IPPV), a method was developed allowing delivery of IPPV by means of nasal prongs (nasal IPPV). A series of 10 newborn infants weighing 1 200 g or less, and requiring nasal IPPV for 5 to 14 days because of intractable apnea has been reported. Five infants survived. With the exception of hearing defects in two survivors, no lesions possibly due to the ventilation procedure were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Attempts were made during this time to develop new techniques for securing the face mask that would decrease the risk of head molding and consequent neurologic complications during NIV. 27 Following the initial description of nasal prongs by Kattiwinkel et al 28 and Caliumi-Pellegrini et al 29 to deliver CPAP, Moretti et al 30 described the first successful application of NIV with bi-nasal prongs in preterm neonates with respiratory failure and apnea. The widespread use of NIV was temporarily hampered following the publication of a paper by Garland et al, 31 who found that neonates ventilated with either oronasal mask or nasal prongs were 30 times more likely to develop gastrointestinal perforations than were neonates ventilated with ETT.…”
Section: Proposed Benefits Of Noninvasive Ventilationmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts were made during this time to develop new techniques for securing the face mask that would decrease the risk of head molding and consequent neurologic complications during NIV. 27 Following the initial description of nasal prongs by Kattiwinkel et al 28 and Caliumi-Pellegrini et al 29 to deliver CPAP, Moretti et al 30 described the first successful application of NIV with bi-nasal prongs in preterm neonates with respiratory failure and apnea. The widespread use of NIV was temporarily hampered following the publication of a paper by Garland et al, 31 who found that neonates ventilated with either oronasal mask or nasal prongs were 30 times more likely to develop gastrointestinal perforations than were neonates ventilated with ETT.…”
Section: Proposed Benefits Of Noninvasive Ventilationmentioning
confidence: 99%
“…48 Additionally, higher inspiratory flow may produce a fast rise in the airway pressure so that the soft palate can be pushed against the tongue and seal the oral cavity, resulting in better breath delivery during an obstructive apnea. 30 IMV augments a neonate's spontaneous respiratory effort or increases "sighing," which may be useful for recruiting and maintaining distal air spaces and preventing apnea.…”
Section: Noninvasive Ventilation Modes In Neonates Nasal Intermittentmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the description of nasal prongs by Kattwinkel et al [3] and Caliumi-Pellegrini et al [4] to deliver NCPAP, in 1981 our group carried out the first successful application of NIPPV with short bi-nasal prongs in 10 very low birth weight (VLBW) infants who had severe apnea spells despite NCPAP and methylxanthines [5]. In most cases the underlying clinical problem was sepsis, and NIPPV was given for 5-14 days.…”
Section: First Trials Of Noninvasive Ventilationmentioning
confidence: 99%
“…The CPAP therapy effects on other organs must be considered too, such as its circula tory effects of increasing venous pressure in the cranium and upper extremities, and a fact known from animal experiments only: that of decreased cardiac stroke volume [1,3,7,18,19,21,23,24,28],…”
Section: Discussionmentioning
confidence: 99%